Impact of the fishing ban on fish diversity and population structure in the middle reaches of the Yangtze River, China - Du, Juan; Tian, Huiwu; Xiang, Zhiyuan; Zhao, Kangshun; Yu, Lixiong; Duan, Xinbin; Chen, Daqing; Xu, Jun; Liu, Mingdian (Frontiers in Environmental Science, 2025)
The Yangtze River has experienced severe ecological degradation due to intensive human activities, including dam construction, land reclamation, and overfishing. These disturbances have disrupted the natural habitats of the Yangtze River, leading to a sharp decline in fish biodiversity and fishery resources. To address this ecological crisis, the Chinese government implemented a 10-year fishing ban in January 2021 to mitigate pressures on fish populations, restore aquatic habitats, and promote biodiversity recovery. The middle reaches of the Yangtze River are characterized by diverse fish species and a critical habitat for aquatic life, this study seeks to assess the effects of the fishing ban on fish diversity, body structure, population and community dynamics in this region. Fish monitoring data collected from 2017–2019 (pre-ban) and 2021–2023 (post-ban) were analyzed to evaluate changes in fish body size, species diversity, and community structure. The analysis results using the PSD method indicate that fish body size has increased following the fishing ban, suggesting the improvement of population structures, and a change in the complexity of food web structure. Species diversity indices showed partial recovery, but the recovery was uneven across different sampling sites. While fish populations showed signs of improvement, particularly in terms of body size and community stability, species diversity remained at relatively low levels in some areas, indicating that full recovery in biodiversity and resource levels may require extended conservation efforts. These findings suggest that while the fishing ban has had a positive initial impact on fish populations and ecological conditions, continued and long-term conservation measures are essential for fully recovering the river’s biodiversity and restoring its fishery resources. The study also highlights the importance of monitoring fish species diversity, body structure, and community dynamics as part of ongoing efforts to evaluate the effectiveness of the fishing ban and refine resource management strategies for the middle reaches of the Yangtze River.